Epidemiology of inflammatory bowel disease in Mexico and Colombia: Analysis of health databases, mathematical modelling and a case-series study - Ciapponi, Agustín (2020)
Background and aims Ulcerative Colitis (UC) and Crohn’s Disease (CD) have a major impact on quality of life and medical costs. The aim of the study was to estimate the prevalence, incidence and clinical phenotypes of Inflammatory Bowel Disease (IBD) cases in Mexico and Colombia. Methods We analyzed official administrative and health databases, used mathematical modelling to estimate the incidence and complete prevalence, and performed a case-series of IBD patients at a referral center both in Mexico and Colombia. Results The age-adjusted complete prevalence of UC per 100,000 inhabitants for 2015/2016 ranged from 15.65 to 71.19 in Mexico and from 27.40 to 69.97 in Colombia depending on the model considered. The prevalence of CD per 100,000 inhabitants in Mexico ranged from 15.45 to 18.08 and from 16.75 to 18.43 in Colombia. In Mexico, the age-adjusted incidence of UC per 100,000 inhabitants per year ranged from 0.90 to 2.30, and from 0.55 to 2.33 in Colombia. The incidence for CD in Mexico ranged from 0.35 to 0.66 whereas in Colombia, the age-adjusted incidence of CD ranged from 0.30 to 0.57. The case-series included 200 IBD patients from Mexico and 204 patients from Colombia. The UC/CD prevalence ratio in Mexico and Colombia was 1.50:1 and 4.5:1 respectively. In Mexico, the female/male prevalence ratio for UC was 1.50:1 and 1.28:1 for CD, while in Colombia this ratio was 0.68:1 for UC and 0.8:1 for CD. In Mexico the relapse rate for UC was 63.3% and 72.5% for CD, while those rates in Colombia were 58.2% for UC and 58.3% for CD. Conclusions The estimated burden of disease of IBD in Mexico and Colombia is not negligible. Although these findings need to be confirmed by population-based studies, they are useful for decision-makers, practitioners and patients with this condition.